Effect of plant growth regulators and pinching on growth and flower yield of African marigold (Tagetes erecta L.) - C T Sathappan (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2018)
Marigold is one of the commercially exploited flower crop that belong to the family Asteraceae. Presently, in our country the commercial extraction of marigold carotenoids is becoming popular in many states. The production of economical yield and better quality of marigold flowers, requires proper crop management techniques. Crop regulation and flower forcing are important techniques to make the marigold production profitable. This can be done by adopting pinching and application of PGRs. Hence, an experiment was carried out in the Department of Horticulture, in factorial randamized block design replicated thrice with 14 treatments with two F1 hybrids viz., Gold Benz tall and Maxima yellow. The experiment comprised of GA3 @ 50, 100 and 150ppm, NAA @ 50, 100 and 150ppm, MH @ 250, 500 and 750ppm, Alar @ 200, 400 and 600ppm and pinching with untreated control. The study revealed that the growth parameter like plant height, number of laterals per plant, number of leaves per plant were significantly influenced by the application of GA3 and NAA. Among the varieties, Gold Benz tall performed better for all the growth attributes but var. Maxima yellow performed better for the number of laterals per plant. The plant sprayed with of GA3 @ 150ppm registered the maximum plant height (70.44cm), number of laterals per plant (16.13), number of leaves per plant (383.76) and leaf area (113.51cm2) and control evinced the least values in the growth parameters. Application of GA3 and NAA significantly enhanced flowering when compared to control, while pinching delayed flowering. The treatment of GA3 @ 150ppm in both Gold Benz tall (30.13 and 406.21 g plant-1) and Maxima yellow (33.16 and 402.83 g plant-1 recorded maximum number of flowers per plant and flower yield respectively as compared to control. Based on the above results, it is revealed that foliar spray of GA3 @ 150 ppm was found to be superior in increasing the yield of flowers in both the varieties.